Pembaharuan pemikiran Islam Tun Dr. Mahathir Mohamad - Dusuki Haji Ahmad, Dato' (Kuala Lumpur : RD Network, 2004)
Thoughts of Mahathir Mohamad on Islam.
In Malay.
Keywords: Mahathir bin Mohamad, -- d. 1925- -- Views on Islam; Islam -- Malaysia; Islam and politics -- Malaysia